2010
DOI: 10.1016/j.ejso.2009.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Identification of residual breast tumour localization after neo-adjuvant chemotherapy using a radioactive 125 Iodine seed

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. M A N U S C R I P T A C C E P T E D ARTICLE IN P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…The brands of the used 125 I‐seeds within this meta‐analysis were limited to: Best Iodine‐125 seed, Best Medical International, Inc. Springfield, VA, USA, distributed by MPM Medical, Freehold, NJ, USA (used by Sung et al) . BrachySource I‐125 seed, BARD Inc, Covington, USA (used by Gobardhan et al, Alderliesten et al, and Donker et al) . Iodine‐125 seed, Cardinal Health, Woodland Hills, CA, USA (used by Gray et al, Hughes et al) . Iodine‐125, Draximage, Montreal, Canada (used by Lovrics et al) . IsoSeed® 125, Bebig Isotopen‐und Medizin Technik, Berlin, Germany (used by Riet et al) . …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The brands of the used 125 I‐seeds within this meta‐analysis were limited to: Best Iodine‐125 seed, Best Medical International, Inc. Springfield, VA, USA, distributed by MPM Medical, Freehold, NJ, USA (used by Sung et al) . BrachySource I‐125 seed, BARD Inc, Covington, USA (used by Gobardhan et al, Alderliesten et al, and Donker et al) . Iodine‐125 seed, Cardinal Health, Woodland Hills, CA, USA (used by Gray et al, Hughes et al) . Iodine‐125, Draximage, Montreal, Canada (used by Lovrics et al) . IsoSeed® 125, Bebig Isotopen‐und Medizin Technik, Berlin, Germany (used by Riet et al) . …”
Section: Resultsmentioning
confidence: 99%
“…Finally, 4208 patients in 16 articles were eligible for inclusion based on the outcome parameters ( Fig. 1, flow chart) [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. After contact with the authors we concluded that only 12 articles included original patients, one article contained original patients and patients from previously reported studies, and three articles contained a patient population that overlapped with previously reported work.…”
Section: Included Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Seeds have a half-life of 60 days, theoretically allowing insertion months prior to surgery if required (e.g., before neoadjuvant chemotherapy). [7, 8] The feasibility of RSL has been reported in institutional series. [9, 10] A small multicenter randomized control trial of WL versus RSL demonstrated no difference in the rates of positive or close margins (p = 0.61), but surgery was shorter following seed localization (mean, 19.4 minutes versus 22.2 minutes, p < 0.001).…”
Section: Introductionmentioning
confidence: 99%
“…Radioguided seed localization is also useful in the neoadjuvant setting. Because of the long half-life of the 125 I-seed (59 days), it can be placed prior to the start of the neoadjuvant chemotherapy while remaining traceable after completion of the chemotherapy regimen [15]. Migration of the seed is rare and high rates of radical excision have been reported both in primary surgery and after neoadjuvant chemotherapy [15,16].…”
Section: Radioguided Seed Localization (Rsl)mentioning
confidence: 99%